PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEAM GEMES TOURNAMENT BERBANTU MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR IPA SEKOLAH DASAR - Utomo, Bagus Ginanjar; Yuliyani, Atik; Wardani, Sri; Widiarti, Nuni; Joko Raharjo, Tri; Harianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to conduct a literature review regarding the use of video media with the Team Games Tournament (TGT) learning model in science learning and also determine the identification and use of the Team Games Tournament learning model in science learning. The method used in the research is the Systematic Literature Review (SLR) method. The results of the analysis of several articles show that the Team Games Tournament Learning Model assisted by learning videos in science learning has a significant positive influence on improving student learning outcomes, understanding concepts, student responses and student activities become more effective.Keywords: Team Gemes Tournament, Science, Learning Results.  Keywords: learning results, science, team gemes tournament